BACTERIA AS A BIO-INDICATOR FOR INTEGRATED COASTAL ZONE MANAGEMENT IN BINH DINH PROVINCE - Thu, Phan Minh; Huong, Le Lan; Thi, Vo Hai (Vietnam Journal of Marine Science and Technology, 2006)
BACTERIA AS A BIO-INDICATOR FOR INTEGRATED COASTAL ZONE MANAGEMENT IN BINH DINH PROVINCE